The impact of activation of the renin-angiotensin system in the development of insulin resistance in experimental models of obesity - Perel, Shireen J. C. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2009.